Stimuli-responsive cellulose nanomaterials for smart applications. (1st May 2020) - Zhu, Qianqian; Liu, Simeng; Sun, Jianzhong; Liu, Jun; Kirubaharan, C. Joseph; Chen, Honglei; Xu, Weihua; Wang, Qianqian
Graphical abstract: Highlights: Recent advances in stimuli-responsive CNMs are reviewed. Reversible interactions of CNMs that trigger desired responses are highlighted. Stimuli-responsive CNMs exhibit great potential as smart materials. Abstract: Stimuli-responsive cellulose nanomaterials (CNMs), which change their physicochemical properties in response to specific stimuli have recently been in the spotlight. A great deal of effort has been dedicated to developing stimuli-responsive CNMs in the past two decades. However, the majority of stimuli-responsive CNMs were achieved via the introduction of stimuli-responsive moieties rather than taking advantage of their inherent switchable hydrogen bonds, electrostatic interactions, and molecular polarization in CNMs. In this review, recent advances and future perspectives of stimuli-responsive CNMs that exploiting the inherent switchable hydrogen bonds, reversible electrostatic interactions, and tunable polarization are highlighted. The principles for designing and assembling such smart CNMs are summarized. Stimuli-responsive CNMs that are sensitive to the changes in humidity, chemical molecules, pH, pressure, and electricity represent tremendous opportunities for making advances in sensors, actuators, biomedical applications due to their sensitivity, specificity, and stability. Additionally, major challenges and future perspectives of stimuli-responsive CNMs are reported.